Mejora del proceso de producción de piezas industriales en la empresa SEFASI E.I.R.L mediante la técnica de las 5S y un plan de mantenimiento preventivo - Nuñez Castillo, Pablo Oscar (2021)
The purpose of the research was to determine which activities do not add value to the product and create delays in the delivery process before its deadlines. To be able to determine this, a 5S plan will be implemented, as well as a preventive maintenance plan to the production line of the workshop, this way we will guarantee the company’s sustainability in an extremely competitive market. The proposals to improve will be focused on the manufacturing of one of the most representative products of the company; however, the benefits will impact on the whole production line as well as the remaining products give the fact that they share the same workstations, and equipment among products. Additionally, a 13-month deadline will be set to implement the necessary tools to develop the 5S plan and the preventive maintenance for the production line. First, an analysis to determine the company’s current situation will take place. Starting from a Value Stream Mapping (VSM), followed by a cause-effect diagram to determine the main causes of the company’s troublesome. Finally, after identifying the main process losses, more improvement opportunities will be identified to employ the selected tools. As a consequence of the improvements, it is expected to reduce the quantity of activities that do not add value to the process to 30% and get machine availability to 90% as the reduction of the quantity of inoperative machine hours during the year. All of the above, will be joined by TIR > COK and an indicator benefit/cost more than 1.